Percepção de discriminação racial em crianças brasileiras - Domingos, Juliana Almeida Rocha (2022)
Combating racial discrimination involves the ability to notice when it occurs. Studies conducted with U.S. children have shown that cognitive, individual and situational factors make some children better at recognizing racial discrimination directed at them or others. Considering the covert manner in which racism operates in Brazil and yet the limited number of studies on the subject in Brazilian psychology, the present study aimed to investigate when and how the perception of racial discrimination in Brazilian children occurs, and whether cognitive aspects (i.e. cultural cognition), contextual variables (i.e. color of the target of discrimination and knowledge about the history of discrimination) and individual variables (i.e., racial belonging) influence this perception. Fifty-three white and black children from 6 to 12 years old participated in this study. Children watched four videos of stories about an adult character who made a choice between a black child and a white child, with the choice always benefiting one over the other. At the end of each story, they had to answer a question about the reasons for the choice made. Participants were divided into three conditions: in Condition 1, they watched videos with stories showing a pattern of racial discrimination in the choices made and which included a situational cue that could justify such attribution; in Condition 2, there was no pattern of racial discrimination in the choices made and there was a situational clue that could justify this; in Condition 3, the stories varied between apparently discriminatory and apparently non-discriminatory choices, and there was no situational cue to aid in the decision. The color of the characters in the stories was not verbalized at any time, and children could only obtain this information by looking at the characters in the video. Participants also performed a racial classification task and provided a racial self-declaration in order to obtain a measure of racial cognition and racial belonging. Results showed participants performed poorly in the perception of racial discrimination task in situations when discrimination was present. An age effect was found only in condition 1 (stories with discrimination) with older children perceiving more discrimination than the younger group. There was no effect of situational variables and group membership on the perception of discrimination in the present sample. We hope this study may contribute to broadening our understanding of the perception of racial discrimination in Brazilian children and provide data that can support future interventions to prevent the occurrence and effects of racial discrimination.